PERAN SAKSI VERBALISANT DALAM PEMBUKTIAN PERKARA PIDANA PERKOSAAN (Studi Kasus di Pengadilan Negeri Klas IA Surakarta) - SULISTIJO, SURJO (2011)
Indonesia is a law-based country, then its social live is unseparatable with law regulations. Realizing a secure, prosper and peaceful life, one of the used mean is by implementing crime code. Objective of crime code is to look for and obtain or at least get closer on material truth, that is complete truth of a crime by implementing the rules of crime code in honest and proper way on the objective to find out who is the actors can be accussed on a crime violation and then ask for investigation and court verdict to obtain the evidence that a crime had conducted and whether the defendant can be stated guilty. Verbalisant witness is not recognized in General Crime Code (KUHAP), but the use of verbalisant witness in Indonesian law context is allowed as long it remains in law corridor. Verbalisant witness can be referred as the investigator who investigating a crime called in court to be heard on his crime-related explanation on problem under-process.